2010
DOI: 10.1002/bies.201000101
|View full text |Cite
|
Sign up to set email alerts
|

Genes that move the window of viability of life: Lessons from bacteria thriving at the cold extreme

Víctor de Lorenzo

Abstract: Whether occurrence of life at the physicochemical extremes results from the entire adaptation of organisms to such settings or it originates from the action of a few genes has been debated for a long time. Recent evidence suggests that a limited number of functions suffice to change the predilection of microorganisms for radically different environmental scenarios. For instance, expression of a few genes from cold-loving bacteria in mesophilic hosts allows them to grow at much lower temperatures and become hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Stabilized MetA proteins partially suppressed the temperature-sensitive phenotype of both dnaK and triple protease deficient mutants. Because improving the growth of E. coli at higher temperatures has an immediate application in realizing the bacterial cell factory, this improvement might also facilitate the identification of target genes and proteins, enabling thermotolerance or improved growth at higher operating temperatures [28-30]. …”
Section: Discussionmentioning
confidence: 99%
“…Stabilized MetA proteins partially suppressed the temperature-sensitive phenotype of both dnaK and triple protease deficient mutants. Because improving the growth of E. coli at higher temperatures has an immediate application in realizing the bacterial cell factory, this improvement might also facilitate the identification of target genes and proteins, enabling thermotolerance or improved growth at higher operating temperatures [28-30]. …”
Section: Discussionmentioning
confidence: 99%
“…Information on the metabolic capabilities of microorganisms at very low temperatures has provided a new perspective on microbial survival strategies in the Earth's cryosphere (12,15,16); however, specific knowledge about their physiology under frozen conditions is still very limited. More precisely, while it is clear that DNA damage and repair are highly relevant to microbial survival, it is not known if microorganisms have the capacity to repair DNA damage under the conditions existing in an ice matrix (i.e., high ionic strength and low water activity and temperature).…”
mentioning
confidence: 99%
“…An interesting proof of principle that such a shift is possible was provided by a study that reported the reduction of the minimal growth temperature of an E. coli strain from 8°C to below 4°C upon the transfer of two chaperonin genes from a psychrophilic bacterium (33). If the genes responsible for this shift of growth range can be transferred to other hosts by horizontal gene transfer, the corresponding traits can move among bacterial species and change their niche specificities (34). Several genes encoding new metabolic functions have been found previously to be horizontally acquired by pathogens, providing a selective advantage in host tissues and access to new niches (35).…”
Section: Discussionmentioning
confidence: 99%